A study on hanging in 167 Cases (Central Medical College Journal, 2023)
Background: Hanging signifies an asphyxiation form which, by a noose or another constricting band tightened by body weight, is secondary to compression or restriction of the neck structures. Death due to hanging is always suicidal until and unless otherwise specified.Objective: To evaluate the socio-demographic characteristics in cases of death due to completed hanging in Bangladesh.Materials and Method: This descriptive study was conducted in the Department of Forensic Medicine, Dhaka Medical College Hospital. The period of study was from July 2020 to June 2022. A total number of 167 autopsies were done during this period on dead bodies that died due to hanging. Points regarding knot of ligature material, injury to neck structures, ligature mark, and stomach condition were noted during post-mortem examinations. All information was noted in a structured data sheet. Data were analyzed using a computer-based programme statistical package for social science (SPSS) for windows version 25.Result: This study shows maximum number of hanging cases 34.1% were in the age group of 21-30 years. Among the 167 suicide cases by hanging, the majority (69.5%) were male. Majority (56.9%) of the cases were married. Family disputes were most common motive 66(39.5%) and in females, the most common motive was marriage related harassment, particularly in married women 38(22.8%). Soft material like cloth, saree, orna, and dupatta was the preferred material for hanging in this study (85.6%) followed by firm materials (7.8%) like a rope. Hard material like iron wires, cable wires, etc were used very rarely (2.4%) and the victims who used these were almost always male.Conclusion: This culture has a great socio-economic burden due to the high incidence of suicidal hanging among young adults. The private essence of hanging and convenient access to ligature points and ligature supplies renders suicide avoidance challenging. Marital disappointment, organic disease issues, and dowry abuse are the primary reasons behind suicide hanging. Social, legal and psychiatric interventions are required to prevent suicide.Central Medical College Journal Vol 6 No 2 Jauly 2022 Page: 77-81